Reading Fluency and Students With Reading Disabilities: How Fast Is Fast Enough to Promote Reading Comprehension?. (March 2018) - O'Connor, Rollanda E.
The goal of improving reading rate and fluency is to positively impact reading comprehension; however, it is unclear how fast students with learning disabilities (LD) need to read to reap this benefit. The purpose of this research was to identify the point of diminishing return for students who were dysfluent readers. Participants included 337 students with reading difficulties in second and fourth grade (61% eligible for special education; 80% with a diagnosis of LD in the area of reading) and 150 typical readers from the same general education classes. LOESS (LOcal regrESSion) plots (logistic regression) were used to determine where linear relations between reading rate and comprehension broke down for these students: the rate at which getting faster no longer contributed clearly to reading comprehension improvement. Although typical readers in this sample showed patterns of oral reading rate and comprehension similar to students in other studies, patterns for students with reading difficulties differed. For dysfluent readers, improving reading rate improved comprehension only in the bands between 35 and 75 words correct per minute in second grade and between 40 and 90 words correct in fourth grade. Reading at faster rates revealed no clear advantage for reading comprehension.